Hydrochemical Assessment of water resources at Baquba City, Diyala Governorate, Eastern Iraq - Hussain, Hiba K.; Al-Shamma, Ayser (Iraqi Journal of Science, 2022)
For hydrochemical assessment of water resources at Baquba City, Diyala Governorate, four surface water samples were collected from the Diyala River and eight groundwater samples inside the city of Baquba. The samples were collected in the two periods, the dry period in October 2018 and the wet period in February 2019. The pH, EC, TH, turbidity, the major ions and trace elements (Fe, Cu, Co, Cd, Pb, Zn and Ni) were investigated. The results showed that the surface and groundwater are turbid, very hard and slightly brackish to moderately saltine in the groundwater, while it is hard to very hard and fresh in surface water. Heavy element analyzes revealed contamination of surface water samples and groundwater with the elements Cadmium, Nickel, Lead, Cobalt and Iron. The water type The water surface and groundwater samples are Na-Ca-Mg-So4- Chloride. The results showed that the water of Baquba is not suitable for human drinking, suitable for irrigation and livestock drinking purposes. According to the sodium adsorption ratio (SAR) and magnesium hazard (MH), all surface and groundwater samples are suitable for irrigation purposes.